How do students write in engineering and the humanities? Intertextuality and metadiscourse in undergraduate dissertations written in Spanish - Navarro, Federico; Montes, Soledad; Álvarez, Martín (Círculo de Lingüística Aplicada a la Comunicación, 2022)
This article aims to contrast metadiscourse and intertextuality in 40 undergraduate dissertations written in Spanish in engineering and the humanities at a Chilean university. Results show that guidance on dissertations’ goals and stages is common across disciplines, especially in introductions, although engineering signals goals more often. All students graduate statements, especially in conclusions, but the frequency of graduation doubles in the humanities. Humanities students prefer hedging over boosting, while boosting is more common in engineering. Self-mentions, especially plural authorial, are frequent in the humanities but do not occur in engineering. Citations are five times more frequent and usually integral in the humanities, while engineering only uses non-integral citations. Indirect speech predominates across disciplines, but direct and mixed speech are also relatively common in the humanities. This study can help to understand undergraduate students’ authorial voices written in Spanish, depict discipline-specific writing choices, and supply data for writing instruction initiatives.